Bruton’s tyrosine kinase inhibitors impair FcγRIIa-mediated platelet responses to bacteria in chronic lymphocytic leukaemia - Naylor-Adamson, Leigh (2021)
Ibrutinib is highly effective in the treatment of chronic lymphocytic leukaemia (CLL), disrupting B cell receptor signalling through the inhibition of Bruton’s tyrosine kinase (Btk). However, ibrutinib has off-target effects, inhibiting platelet aggregation with associated haemorrhage. More recently, second generation Btk inhibitors have been developed to be more specific for Btk, including acalabrutinib. Still, acalabrutinib is similarly associated with a bleeding risk. Treatment of CLL with ibrutinib is also connected to an increased infection risk. Though platelets are known for their role in haemostasis, they additionally play a key role in innate immunity. Platelets can interact with bacteria through a variety of mechanisms, with one such mechanism being the FcγRIIa receptor, a low affinity IgG immune receptor that can mediate platelet aggregation, phagocytosis, and release of bactericidal substances. Btk, and potentially other Tec family kinases, is a key component of the FcγRIIa intracellular signalling pathway. However, the role of these kinases in FcγRIIa signalling in response to bacteria is unknown. Moreover, the effects of iBtks on platelet responses to bacteria have not been evaluated. This study aims to investigate the role of Btk in platelet FcγRIIa signalling in response to bacterial agonists, and how this is affected by ibrutinib. We show that ibrutinib and acalabrutinib inhibit healthy donor FcγRIIa-mediated platelet aggregation, alpha and dense granule release, in response to incubation with Staphylococcus aureus and Escherichia coli, and in response to FcγRIIa crosslinking with the anti-FcγRIIa monoclonal antibody IV.3. Moreover, we show platelets derived from ibrutinib-untreated CLL patients aggregate normally to bacteria in the presence of autologous plasma. However, platelets from ibrutinib-treated CLL patients have significantly inhibited aggregation, alpha granule release and bacteria scavenging. Platelet surface levels of FcγRIIa remained unchanged in both CLL groups, compared to healthy controls, however, levels of GPVI and αIIbβ3 were decreased in CLL samples regardless of ibrutinib therapy. In both healthy control and ibrutinib-untreated CLL platelets, phosphorylation of Btk at tyrosine 223 (a marker of Btk activation) was detected in response to FcγRIIa agonists including Staphylococcus aureus and Escherichia coli. In contrast, Btk phosphorylation at Y223 in response to bacteria was absent in ibrutinib-treated CLL platelets, and in healthy controls platelets inhibited by ibrutinib and acalabrutinib in vitro. We also show a significant decrease in Tec phosphorylation in healthy control platelets treated with ibrutinib, and in ibrutinibtreated CLL platelets. To determine if Btk was required for platelet bacteria responses, X-linked agammaglobulinaemia platelets, which lack a functional Btk, were exposed to bacteria and FcγRIIa-mediated platelet aggregation was observed, showing Btk to be unessential. To conclude, our data shows that iBtks impair FcγRIIa-mediated platelet responses to bacteria both in vitro and at therapeutic conditions, and this impairment may be a result of both Btk and Tec inhibition, though potential off-target effects on other kinases cannot be dismissed. The effect of iBtks on platelet immune responses may possibly contribute to increase infections observed in CLL.
HydraID: hull:18521 Hydra Discover Access Group: public ETD Collection: ETDHullYorkMedicalSchool
Keywords: Medicine